Efficient polymer solar cells based on poly(thieno[2, 3-f]benzofuran-co-thienopyrroledione) with a high open circuit voltage exceeding 1 V. (November 2017) - Gao, Yueyue; Saparbaev, Aziz; Zhang, Yong; Yang, Renqiang; Guo, Fengyun; Yang, Yulin; Zhao, Liancheng
Abstract: A new donor-acceptor type conjugated polymer (PTBFTPD) based on two-dimensional (2D) conjugated alkylthienyl substituted thieno[2, 3- f ]benzofuran (TBF) and thienopyrroledione (TPD) unit, was synthesized and applied as donor material for bulk heterojunction polymer solar cells. As a comparison, its counterpart conjugated polymer (PBDTTPD) based on alkylthienyl substituted thieno[2, 3- f ]benzothiophene (BDT) and TPD unit, was also synthesized. The thermal properties, optical and electrochemical properties, energy levels, molecular chain orientation stacking behavior and photovoltaic properties of two polymers were intensively investigated. Both polymers showed similar optical properties. Compared with PBDTTPD, PTBFTPD shown the similar absorption properties in solution and in a thin film. PTBFTPD had a slightly narrow bandgap of 1.83 eV while that of 1.85 eV for PBDTTPD. PTBFTPD displayed a deeper highest occupied molecular orbital (HOMO) energy level of (−5.64 eV), which was 0.1 eV lower than that for PBDTTPD. The XRD study showed that PTBFTPD possessed a closer π-π stacking than PBDTTPD. The photovoltaic properties were investigated under various conditions, the optimized power conversion efficiency (PCE) of 4.33% with an open-circuit voltage (Voc ) of as high as 1.09 V were obtained, which resulted in a 32% improvement in comparison with PBDTTPD/PC71 BM-based device under the same conditions. Graphical abstract: Highlights: A novel polymer (PTBFTPD) based on thieno[2, 3- f ]benzofuran (TBF) and thienopyrroledione (TPD) was designed and synthesized. The closer π-π stacking of PTBFTPD film was found compared to that of PBDTTPD. A promising power conversion efficiency of 4.33% based on PTBFTPD/PC71BM was obtained.